2005
DOI: 10.1039/b501846c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a cytochrome c–nitrous oxide reductase complex is obligatory for N2O reduction by Paracoccus pantotrophus

Abstract: Nitrous oxide reductase (N 2 OR) catalyses the final step of bacterial denitrification, the two-electron reduction of nitrous oxide (N 2 O) to dinitrogen (N 2 ). N 2 OR contains two metal centers; a binuclear copper center, Cu A , that serves to receive electrons from soluble donors, and a tetranuclear copper-sulfide center, Cu Z , at the active site. Stopped flow experiments at low ionic strengths reveal rapid electron transfer (k obs = 150 s −1 ) between reduced horse heart (HH) cytochrome c and the Cu A cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 33 publications
4
39
1
Order By: Relevance
“…Small electron donor proteins, as c-type cytochromes, either physiological or nonphysiological (mitochondrial cytochrome c), have been used as electron donors to N 2 OR in in vitro assays [81]. In the case of N 2 OR isolated from Rhodobacter capsulatus, Rhodobacter sphaeroides f. sp.…”
Section: Catalytic Properties Of Cuz and Reaction Intermediatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small electron donor proteins, as c-type cytochromes, either physiological or nonphysiological (mitochondrial cytochrome c), have been used as electron donors to N 2 OR in in vitro assays [81]. In the case of N 2 OR isolated from Rhodobacter capsulatus, Rhodobacter sphaeroides f. sp.…”
Section: Catalytic Properties Of Cuz and Reaction Intermediatesmentioning
confidence: 99%
“…In the case of N 2 OR isolated from Rhodobacter capsulatus, Rhodobacter sphaeroides f. sp. denitrificans, and Paracoccus pantotrophus [37,82,83], the physiological donor is a periplasmic c-type cytochrome, but Paracoccus pantotrophus N 2 OR can also accept electrons from a periplasmic type 1 copper protein, pseudoazurin [37], and from the mitochondrial horse heart cytochrome c [81]. Bovine heart cytochrome c is able to reduce Achromobacter cycloclastes N 2 OR [84], but its physiological electron donor is pseudoazurin [85].…”
Section: Catalytic Properties Of Cuz and Reaction Intermediatesmentioning
confidence: 99%
“…This high homology justifies not only the use of the P. panthotropus pseudoazurin structure in the docking studies, but also the use of the biochemical properties of P. panthotropus N 2 OR. It was reported that the increase in ionic strength decreases the activity of P. panthotropus N 2 OR in the presence of horse heart cytochrome c, which is an indication that the complex formed has an electrostatic nature [22]. The Fig.…”
Section: General Analysismentioning
confidence: 99%
“…Previously, direct electron transfer studies have shown for P. panthotropus and P. nautica N 2 OR that the small electron transfer proteins donate electrons directly to the binuclear CuA center of N 2 OR [18,22]. Therefore, the solutions were filtered using the condition that the distance between the redox centers, the CuA center and the iron ion of cytochrome c, or the copper ion of pseudoazurin, should be less than 20 Å , a condition required for an efficient electron transfer [15] (Table 1, and their representation is shown in Figs.…”
Section: General Analysismentioning
confidence: 99%
See 1 more Smart Citation